AGE, GROWTH, LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION IN HILSA, TENUALOSA ILISHA (HAMILTON) FROM THE HOOGHLY ESTUARINE SYSTEM - De, D K; Datta, N C (Indian Journal of Fisheries, 2011)
The age and growth of Indian shad, Tenualosa ilisha (Hamilton) commonly known as hilsa, of thefreshwater zone of Hooghly estuary were studied by using the length- frequency method. The averagesizes attained by hilsa were found to be 18.9, 27.7,35.1, 41.3, 46.6 and 51.1 an at the end of 1 to 6 yearsrespectively. The von Bertalanffy growth equation for this species was estimated asL, = 75.13 [1-eO""3 M*"Â» ]The length -weight relationships of hilsa were also studied based on the specimens measuring 20-552 mmin length. The results of the analysis of covariance showed that there was significant difference withregard to regression coefficients between the sexes and therefore separate equations were obtained formale:Log W = -4.6821 + 2.9066 Log L and forFemale : Log W = - 4.4080 + 2.8083 Log L.The relative condition 'Kn' at different lengths (180-552 mm) of fish and during different months of theyear was estimated. The first low value of 'Kn' around 345 mm size group was found to be the lowestand this size range might be associated with the first spawning in the life of the fish. The significancein the fluctuation in 'Kn' values was discussed.